Highly Dispersed Cobalt Nanoparticles Embedded in Nitrogen-Doped Graphitized Carbon for Fast and Durable Potassium Storage - Xiaodong Shi; Zhenming Xu; Cheng Han; Runze Shi; Xianwen Wu; Bingan Lu; Jiang Zhou; Shuquan Liang (Nano-Micro Letters, 2020)
Abstract Potassium-ion batteries (KIBs) have great potential for applications in large-scale energy storage devices. However, the larger radius of K+ leads to sluggish kinetics and inferior cycling performance, severely restricting its practical applicability. Herein, we propose a rational strategy involving a Prussian blue analogue-derived graphitized carbon anode with fast and durable potassium storage capability, which is constructed by encapsulating cobalt nanoparticles in nitrogen-doped graphitized carbon (Co-NC). Both experimental and theoretical results show that N-doping effectively promotes the uniform dispersion of cobalt nanoparticles in the carbon matrix through Co–N bonds. Moreover, the cobalt nanoparticles and strong Co–N bonds synergistically form a three-dimensional conductive network, increase the number of adsorption sites, and reduce the diffusion energy barrier, thereby facilitating the adsorption and the diffusion kinetics. These multiple effects lead to enhanced reversible capacities of 305 and 208.6 mAh g−1 after 100 and 300 cycles at 0.05 and 0.1 A g−1, respectively, demonstrating the applicability of the Co-NC anode for KIBs.